PENGETAHUAN, SIKAP, DAN KESIAPSIAGAAN KADER SIAGA BENCANA DALAM MENGHADAPI BENCANA BANJIR - Zuliani Zuliani; Sufendi Hariyanto (Jurnal EDUNursing, 2021)
Abstract  Knowledge of standby cadres about earthquake disaster management is very important in disaster preparedness. In order not to panic and have a negative impact on them. The purpose of this study was to determine the knowledge, attitudes, and preparedness of disaster preparedness cadres in dealing with flood disasters. The research method was carried out using quantitative descriptive research methods. The population in this study were all existing cadres in Ngresik Regency, totaling 51 respondents based on data from BPBD Gresik Regency in 2019 using consecutive sampling, while the research sample used total sampling. Research time in September 2020. Research using a questionnaire sheet with quantitative data analysis. Respondents are knowledgeable and have good attitude and are ready to face flood disasters. Keyword: knowledge, attitude, preparedness, flood disaster